Power Efficiency with Optimized Power Routing and Dedicated Path Protection in Elastic Optical Networks - Chandra Jaiswal, Deo; Asthana, Rachna (International Journal of Engineering and Technology, 2018)
In the current era, the power consumption increases as per increased demand. So it creates the necessity to reduce power consumption wherever feasible. Â Due to the flexible nature of bandwidth allocation and efficient spectral design, elastic optical networks (EONs) are leading transmitter of traffic data. To ensure the seamless flow of these traffic data, network survivability is the quintessential requirement. In order to achieve the high level of survivability, dedicated path structures due to fast switching time are utilized with additional backup resources. The power consumed by these backup resources is also increased. Shortest path routing (SPR) is the prominent method applied to achieve power efficiency in EONs against single link failure. Power efficient dedicated path protection with optimized power routing (OPR) in single link failure is elaborated in this paper to resolve the power saving issues. An Integer Linear Programming (ILP) model is formed to optimize the required power that needs to concern the optimized power path and power efficient dedicated path allocation. The maximum network components that are in an idle state switch into sleep / off mode optimizes required power. The evaluation results strongly illustrate that applied OPR improves power saving during low traffic than SPR with the dedicated path protection. In addition, overall required power saturates when there are enormous traffic demands.Â Â